Analisis Laporan Keuangan pada UMKM Berdasarkan Standar Akuntansi Keuangan EMKM: Studi Kasus UMKM 21Labels - Salsabilla, Keizha Venda; Yusman, Rannisa Aliya; Simangunsong, Naomi Oktavia; Reinaldi Farid; Kurniati, Fitrina (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to implement accounting records in 21Labels MSMEs engaged in online clothing trading, which previously did not use a financial recording system in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The method used in this study is a quantitative descriptive method with data collection through interviews and financial statement analysis. The results of the study show that after implementing structured accounting records, 21Labels MSMEs managed to record a net profit of IDR1,609,107 in the September 2024 period. In addition, the financial position report shows that the company has a healthy financial structure, with total assets of IDR10,609,107 which are fully financed by equity. This study shows that the implementation of proper accounting records can help MSMEs in managing finances and improving operational efficiency, as well as strengthening the company's capital position.